2022
DOI: 10.3390/membranes12070719
|View full text |Cite
|
Sign up to set email alerts
|

Small Intestinal Submucosa Biomimetic Periosteum Promotes Bone Regeneration

Abstract: Background: Critical bone defects are a significant problem in clinics. The periosteum plays a vital role in bone regeneration. A tissue-engineered periosteum (TEP) has received increasing attention as a novel strategy for bone defect repairs. Methods: In this experiment, a biomimetic periosteum was fabricated by using coaxial electrospinning technology with decellularized porcine small intestinal submucosa (SIS) as the shell and polycaprolactone (PCL) as the core. In vitro, the effects of the biomimetic perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Electrospinning is a popular scaffold fabrication technique that enables the design and fabrication of nanofiber scaffolds similar to natural ECM [ 187 , 188 ]. In this method, the polymer melt or solute is first poured into a syringe with a capillary tube, and under a high-voltage electric field, the polymer fluid overcomes surface tension to flow in the direction of the electric field, resulting in long and thin threads, and finally, nanofibers are stably deposited on the substrate to form the scaffold.…”
Section: Scaffold Fabrication Methodsmentioning
confidence: 99%
“…Electrospinning is a popular scaffold fabrication technique that enables the design and fabrication of nanofiber scaffolds similar to natural ECM [ 187 , 188 ]. In this method, the polymer melt or solute is first poured into a syringe with a capillary tube, and under a high-voltage electric field, the polymer fluid overcomes surface tension to flow in the direction of the electric field, resulting in long and thin threads, and finally, nanofibers are stably deposited on the substrate to form the scaffold.…”
Section: Scaffold Fabrication Methodsmentioning
confidence: 99%
“…The results of the studies showed the ability of SP-loaded SIS/PCLA sheet to recruit cells and promote wound healing. Furthermore, coaxial electrospinning technology was also used to create a bionic periosteum consisting of a shell made of SIS and a nucleus made of PCL [ 87 ]. The fibers of the biomimetic periosteum are arranged in parallel and have a distinct core-shell structure.…”
Section: Overview Of Sismentioning
confidence: 99%